H3K27ac-activated LncRNA NUTM2A-AS1 Facilitated the Progression of Colorectal Cancer Cells via MicroRNA-126-5p/FAM3C Axis - Lin, Haiguan; Hu, Shidong; Li, Yuxuan; Li, Songyan; Teng, Da; Yang, Yan; Liu, Boyan; Du, Xiaohui (Current Cancer Drug Targets, 2024)
Objective: Long non-coding RNAs (lncRNAs) are of great importance in the process of colorectal cancer (CRC) tumorigenesis and progression. However, the functions and underlying molecular mechanisms of the majority of lncRNAs in CRC still lack clarity. Methods: A Quantitative real-time polymerase chain reaction (qRT-PCR) was employed to detect lncRNA NUTM2A-AS1 expression in CRC cell lines. Cell counting kit 8 (CCK-8) assay and flow cytometry were used to examine the biological functions of lncRNA NUTM2A-AS1 in the proliferation and apoptosis of CRC cells. RT-qPCR and western blot were implemented for the detection of cell proliferation-, apoptosis-related proteins, and FAM3C. Bioinformatics analysis and dual- luciferase reporter assays were utilized to identify the mutual regulatory mechanism of ceRNAs. Results: lncRNA NUTM2A-AS1 notably elevated in CRC cell lines and the silenced of NUTM2A- AS1 declined proliferation and facilitated apoptosis. Mechanistically, NUTM2A-AS1 was transcriptionally activated by histone H3 on lysine 27 acetylation (H3K27ac) enriched at its promoter region, and NUTM2A-AS1 acted as a sponge for miR-126-5p, leading to the upregulation of FAM3C expression in CRC cell lines. Conclusion: Our research proposed NUTM2A-AS1 as an oncogenic lncRNA that facilitates CRC malignancy by upregulating FAM3C expression, which might provide new insight and a promising therapeutic target for the diagnosis and treatment of CRC.
Keywords: miR-126-5p